Government regulations and power advantage shifting in buyer-supplier exchange relation: the case of the shisha industry in Singapore / Ameen Ali Talib. - Ali Talib, Ameen (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Government regulations can have a direct impact on the power advantages enjoyed by buyers and/or suppliers in exchange interaction. Exchange power can be defined as a function of the relative utility and relative scarcity of the resources brought to the transaction by each of the parties involved (Cox et al., 2000). The state can play a central role in creating and sustaining situations of resource scarcity through its ability to grant property rights and through regulations. This scarcity can create a power advantage in buyer-supplier relation. Sanderson (2001) referred to government as simply a creator and guarantor of resource scarcity as creative regulation, and referred to government role in containing or removing an existing power advantage as disruptive regulation. We argue there is another form of regulation effect called disruptive-creative regulation. We present a case study of the shisha industry in Singapore where regulations alter the supplier-buyer power advantage and illustrates a situation where licenses in a competitive market are revoked (disruptive regulation) that creates an oligopoly; albeit a temporary one. The case study also illustrates how competition in the shisha industry has led to price-stagnation war and kinked demand. Regulations shifted the power advantage in a competitive market to the suppliers; however the case study illustrates how by suppliers not taking advantage of the resource scarcity have led to suppliers returning the power advantage to buyers. The paper adds to the theoretical understanding of government regulation interfering in supplier-buyer exchange relations in competitive markets, shifting power advantages and highlights how, as was the case in the case study, suppliers at times are not able to view resource scarcity as a power advantage to them due to game playing. Four decades ago, in 1974, Professor Henry G. Manne testified before the Senate Subcommittee on Anti-Trust and Monopoly and his closing remarks were “Now with a fearful sense that there may in fact be no one left to listen or to act, I would still urge this Committee to forcefully reject any new regulatory gimmicks, and to get down to the much more serious task of freeing (American) competition from its single most serious opponent, the (US) government.” (Barron’s National Business and Financial Weekly, May 20, 1974 Editorial Commentary : ‘Myth of Monopoly: Only the Government Can Hobble Competition”)